2010
DOI: 10.1007/s00394-010-0155-2
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and energy homeostasis was not affected in C57BL/6 mice fed high whey protein or leucine-supplemented low-fat diets

Abstract: We suggest that an exposure of mice to HP diets or a corresponding leucine supplementation has no significant effect on energy homeostasis and UCP expression compared with AP diets when feeding a low-fat diet. The use of high-quality whey protein might at least in part explain the results obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 31 publications
3
34
0
1
Order By: Relevance
“…It has been shown that HPD has affected blood glucose tolerance (Honors et al 2012), leading to the stimulation of genes involved in glyconeogenesis to ensure the regulation of glycemic control (Blouet et al 2006). Similar to our result, Noatsch et al (2011) found a significant increase in blood glucose levels of C57BL/6 mice fed a HPD over 14 weeks in a study investigating the effects of a HPD on body weight and energy homeostasis.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that HPD has affected blood glucose tolerance (Honors et al 2012), leading to the stimulation of genes involved in glyconeogenesis to ensure the regulation of glycemic control (Blouet et al 2006). Similar to our result, Noatsch et al (2011) found a significant increase in blood glucose levels of C57BL/6 mice fed a HPD over 14 weeks in a study investigating the effects of a HPD on body weight and energy homeostasis.…”
Section: Discussionsupporting
confidence: 93%
“…Protein was extracted from skeletal muscle (quadriceps and gastrocnemius), as described previously (39). Sodium dodecyl sulfate polyacrylamide gel electrophoresis and incubation of different antibodies, as well as chemiluminescence detection and quantification of protein bands, were done as described before (39) Analyses of fatty acid oxidation. Assays were done essentially as described (2,9).…”
Section: Methodsmentioning
confidence: 99%
“…However, the subject remains controversial because the results available do not unequivocally confirm the antiobese role of leucine feeding and of leucine signaling mechanisms [12,13]. Recently, we showed that mice kept on normal-fat diets with different whey protein and leucine concentrations for 14 weeks showed no differences in body weight (BW) gain [14]. In contrast, Zhang et al [15] found a reduced weight gain and improved glucose homeostasis when high-fat diets were used and leucine was supplemented via drinking water.…”
Section: Introductionmentioning
confidence: 95%
“…Circulating nonesterified fatty acids (NEFA), plasma cholesterol and triacylglycerol (TG) concentrations in plasma and liver were determined as previously described [14]. Free amino acid concentrations in plasma were determined by HPLC according to published protocols [17].…”
Section: Blood and Tissue Measurementsmentioning
confidence: 99%